DINASTI FATHIMIYAH DI MESIR (Analisa Pertumbuhan, Perkembangan dan Pengaruhnya) - Rahmadi, Fuji (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2017)
Fathimiyah dynasty is one of the Islamic dynasty that ever existed and also has a share in enriching the history of Islamic civilization. If the horizontal line drawn the history of Islamic civilization, it will be known that of the many Islamic histories contained in the books of history of civilization there is much bloodshed just to uphold and maintain leadership.